PENERAPAN SMART CONTRACT UNTUK PENGELOLAAN ASET DI INSTITUT TEKNOLOGI BACHARUDDIN JUSUF HABIBIE - Syafira Fatwa; Rakhmadi Rahman (CV. Denasya Smart Publisher, 2024)
This research explores the application of blockchain technology and smart contracts as an innovative solution to improve asset management at the Bacharuddin Jusuf Habibie Institute of Technology (ITH). By utilizing blockchain, this research aims to increase security, transparency and efficiency of asset management through decentralizing data storage and automating transaction execution. A comprehensive literature review and network design using Cisco tools were used to build a reliable and secure network infrastructure to support the implementation of blockchain technology. Conventional asset management processes often face challenges such as security risks, lack of transparency, and administrative inefficiencies. Blockchain offers a solution by providing a system that is resistant to change (immutability), decentralization, and automation through smart contracts. The results of this research show that the use of blockchain technology at ITH improves network connectivity, strengthens security measures, and simplifies the asset management process. Implementing firewalls and NAT in network design plays an important role in protecting data and maintaining system integrity. The study also identified several challenges, including the need for adequate staff training and infrastructure improvements to support this technology on an ongoing basis. Recommendations for future implementation include intensive training for staff regarding blockchain technology, improving network infrastructure, regular evaluation of already implemented systems, and adding layers of security to ensure optimal data protection. With these steps, it is hoped that ITH can maximize the benefits of blockchain technology in managing campus assets, as well as providing an example for other educational institutions in adopting this technological innovation.